2017
DOI: 10.3390/nu9050490
|View full text |Cite
|
Sign up to set email alerts
|

Desalted Duck Egg White Peptides Promote Calcium Uptake and Modulate Bone Formation in the Retinoic Acid-Induced Bone Loss Rat and Caco-2 Cell Model

Abstract: Desalted duck egg white peptides (DPs) have been proven to promote calcium uptake in Caco-2 cells and rats treated with a calcium-deficient diet. The retinoic acid-induced bone loss model was used to evaluate the effect of DPs on calcium absorption and bone formation. Three-month-old Wistar female rats were treated with 0.9% saline, DPs (800 mg/kg), or alendronate (5 mg/kg) for three weeks immediately after retinoic acid treatment (80 mg/kg) once daily for two weeks. The model group was significantly higher in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…The breaking strength was determined with a three-point bending test using a texture analyzer system TA.XTPlus (Stable Micro System, Surrey, England). 24 The femur sample was placed on two vertically parallel supports (spacing, 8 mm) with the larger side on top. Then, a load was applied to the midshaft of the femur with a constant deformation rate of 5 mm/min until a fracture occurred.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The breaking strength was determined with a three-point bending test using a texture analyzer system TA.XTPlus (Stable Micro System, Surrey, England). 24 The femur sample was placed on two vertically parallel supports (spacing, 8 mm) with the larger side on top. Then, a load was applied to the midshaft of the femur with a constant deformation rate of 5 mm/min until a fracture occurred.…”
Section: ■ Introductionmentioning
confidence: 99%
“…To improve the utilization of salted duck egg white, desalted duck egg white peptides (DPs) were prepared by electrodialysis and enzymatic hydrolysis. DPs were proved to effectively promote calcium absorption and bone strength (Zhao et al., 2014), which may be attributed to opening the transient receptor potential vanilloid 6 (TRPV6) calcium channel (Hou, Liu, Kolba, Guo, & He, 2017). DPs could also improve the calcium absorption in the presence of phytic acid by regulating enterocytes differentiation and avoid calcium precipitate in gut (Hou, Liu, Shi, Ma, & He, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Calcium binding peptides could interact with Ca 2+ during the formation of the peptide-calcium complex [ 8 ], which was believed to be a suitable candidate for calcium supplementation [ 9 ]. In the recent decade, calcium binding peptides and the peptide-calcium complex have attracted great attention and many food proteins have been explored to prepare and isolate calcium binding peptides, including tilapia protein [ 10 ], Antarctic krill protein [ 11 ], Pacific cod skin protein [ 12 ], whey protein [ 13 ], duck egg white [ 14 ], etc. Furthermore, previous studies reported that fishbone derived peptides also possess high calcium binding activity and can improve calcium bioavailability [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%